The Adhesion Mechanism of Marine Mussel Foot Protein: Adsorption of L-Dopa on α- and β-Cristobalite Silica Using Density Functional Theory - Shabeer Ahmad Mian; Younas Khan (Journal of Chemistry)
Marine mussels strongly adhere to various surfaces and endure their attachment under a variety of conditions. In order to understand the basic mechanism involved, we study the adsorption of L-dopa molecule on hydrophilic geminal and terminal isolated silanols of silica (001) surface. High content of modified amino acid L-dopa is found in the glue-like material secreted by the mussels through which it sticks to various surfaces under water. To understand the adsorption behavior, we have made use of periodic Density Functional Theory (DFT) study. The L-dopa molecule adheres to silica surfaces terminated with geminal and terminal silanols via its catechol part. In both cases, the adhesion is achieved through the formation of 4 H-bonds. A binding energy of 29.48 and 31.67 kcal/mol has been estimated, after the inclusion of dispersion energy, for geminal and terminal silanols of silica, respectively. These results suggest a relatively stronger adhesion of dopa molecule for surface with terminal isolated silanols.